The postponement of Tokyo Olympics 2020: An ethical dilemma concerning the expiration of banned period of doping-banned athletes - Chaudhuri, B. R. (SAGE Business Cases, 2022)
The International Olympic Committee (IOC) and the Tokyo Organizing Committee had to postpone the 2020 Tokyo Olympics due to the COVID-19 pandemic`s global outbreak. While reorganizing for the Olympics in 2021, the decisionmakers must consider several critical operational, and ethical issues. One issue relating to athletes` participation in the changed set of participants has significant functional, ethical, behavioural, and psychological impacts. Further, it impacts implementing the fundamental principles of Olympism, or the Olympic Movement, like solidarity and non-discrimination.